Clinico-immunological efficiency of age-related skin changes correction by neofibrolifting - Tsepkolenko, H. V. (Zaporozhye Medical Journal, 2019)
The aim of the work is to develop a procedure for isolation of lymphocytes from biopsied skin samples, to study the content of CD4 + and CD8 + cells of αβT-lymphocytes subpopulations in patients of different age groups in the process of neofibrolifting and to evaluate the possible role of the skin immune system in achieving an effective clinical result by the indicated method of involutional changes correction. Materials and methods. In total, 99 patients of different ages with signs of skin chrono- and photoageing on the face who visited the Clinic “Virtus” were examined and treated. Clinical and dermatological examinations were conducted, as well as neofibrolifting with the sequential intradermal administration of platelet-rich plasma (PRP) and dermal autofibroblasts (DFBs). PRP was prepared by standard centrifugation on a Harvest Smart PReP2 special centrifuge. DFBs were obtained from biopsied skin samples of the postaural area and accumulated ex vivo in the biotechnological laboratory. Lymphocytes from the skin biopsies were isolated by enzymatic treatment. Phenotyping of cells for CD4 and CD8 antigens was performed by flow cytofluorimetry. Results. It was established that the clinical manifestation of involutional changes in the skin is accompanied by a decrease in the number of CD4 + and CD8 + lymphocytes. As a result of neofibrolifting, a significant clinical correction of age-related disorders is observed. At the same time, the number of CD4+ cells increases within 2 weeks of the PRP administration and increases further as a result of autofibroblasts transplantation and remains at a high level over the entire follow-up period (12 months). The number of CD8 + lymphocytes in the skin is changed in the opposite direction. The clinical improvement was clearly pronounced after autofibroblast transplantation and throughout the 12-month period. Conclusions. The number of CD4+ and CD8+ cells in patients aged 45-55 and 56 years and older is significantly reduced compared with the indices of younger patients, which indicates aging of the skin T-cell immunity. As a result of neofibrolifting, there is a significant increase in the number of CD4+ lymphocytes after the PRP introduction followed by an increase in their level due to autotransplantation of fibroblasts, which remains significantly higher than baseline for 12 months. The number of CD8+ lymphocytes changes in the opposite direction. The results indicate that the skin immune system is partly involved in the implementation of neofibrolifting mechanisms.